DLG1 functions upstream of SDCCAG3 and IFT20 to control ciliary targeting of polycystin-2 - Rezi, Csenge K.; Aslanyan, Mariam G; Diwan, Gaurav; Cheng, Tao; Chamlali, Mohamed; Junger, Katrin; Anvarian, Zeinab; Lorentzen, Esben; Pauly, Kleo B; Afshar-Bahadori, Yasmin; Fernandes, Eduardo FA; Qian, Feng; et al. (EMBO reports, 2024)
Polarized vesicular trafficking directs specific receptors and ion channels to cilia, but the underlying mechanisms are poorly understood. Here we describe a role for DLG1, a core component of the Scribble polarity complex, in regulating ciliary protein trafficking in kidney epithelial cells. Conditional knockout of Dlg1 in mouse kidney causes ciliary elongation and cystogenesis, and cell-based proximity labeling proteomics and fluorescence microscopy show alterations in the ciliary proteome upon loss of DLG1. Specifically, the retromer-associated protein SDCCAG3, IFT20, and polycystin-2 (PC2) are reduced in the cilia of DLG1-deficient cells compared to control cells. This phenotype is recapitulated in vivo and rescuable by re-expression of wild-type DLG1, but not a Congenital Anomalies of the Kidney and Urinary Tract (CAKUT)-associated DLG1 variant, p.T489R. Finally, biochemical approaches and Alpha Fold modelling suggest that SDCCAG3 and IFT20 form a complex that associates, at least indirectly, with DLG1. Our work identifies a key role for DLG1 in regulating ciliary protein composition and suggests that ciliary dysfunction of the p.T489R DLG1 variant may contribute to CAKUT.